Astrochemistry and Astrobiology - Smith, Ian W. M.; Cockell, Charles S.; Leach, Sydney; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Astrochemistry and Astrobiology is the debut volume in the new series Physical Chemistry in Action. Aimed at both the novice and experienced researcher, this volume outlines the physico-chemical principles which underpin efforts to understand astrochemistry and predict astrobiology. An introductory chapter includes fundamental aspects of physical chemistry required for understanding the field. Eight further chapters address specific topics, encompassing basic theory and models, up-to-date research and an outlook on future work. The last chapter examines each of the topics addressed from a different angle. Written and edited by international experts, this text is accessible for those entering the field of astrochemistry and astrobiology, whilst still providing new information and insights for experienced researchers.
Aspects of Physical Chemistry -- The Molecular Universe -- Chemical Processes in the Interstellar Medium -- Astrochemistry: Synthesis and Modelling -- Planetary Atmospheres and Chemical Markers for Extraterrestrial Life -- The Importance of Water -- Life, Metabolism and Energy -- Life: The Physical Underpinnings of Replication -- Physical Chemistry.
Keywords: Chemistry; Chemistry, Physical organic; Astronomy; Astrobiology; Chemistry; Physical Chemistry; Astrobiology; Theoretical and Computational Chemistry; Astronomy, Astrophysics and Cosmology